2022
DOI: 10.1021/acs.est.2c04181
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Aerosol Emissions in a CO2 Capture System: Combining Aerosol Formation Inhibition and Wet Electrostatic Precipitation

Abstract: Aerosol emission from the CO 2 capture system has raised great concern for causing solvent loss and serious environmental issues. Here, we propose a comprehensive method for reducing aerosol emissions in a CO 2 capture system under the synergy of aerosol formation inhibition and wet electrostatic precipitation. The gas−solvent temperature difference plays a vital role in aerosol formation, with aerosol emissions of 740.80 mg/m 3 at 50 K and 119.36 mg/m 3 at 0 K. Different effects of SO 2 and SO 3 on aerosol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…In the water wash section, the large aerosols were intercepted with decreasing number concentrations, while the small aerosols increased in number due to condensation. In addition, compared to other studies 10,12,17 where the aerosol median diameter was concentrated in the 0.1−1 μm range, the median aerosol size in this study was larger, implying that the capture was more easily achieved. The discrepancy could be explained by the larger amount of solvent and more adequate absorption reaction in the MSC absorber.…”
Section: ■ Results and Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…In the water wash section, the large aerosols were intercepted with decreasing number concentrations, while the small aerosols increased in number due to condensation. In addition, compared to other studies 10,12,17 where the aerosol median diameter was concentrated in the 0.1−1 μm range, the median aerosol size in this study was larger, implying that the capture was more easily achieved. The discrepancy could be explained by the larger amount of solvent and more adequate absorption reaction in the MSC absorber.…”
Section: ■ Results and Discussioncontrasting
confidence: 75%
“…For instance, Khakharia et al found that the total emission of MEA ranged from 1200 to 1900 mg/m 3 at aerosol number concentrations of 1.4–1.7 × 10 8 1/cm 3 . In our previous research, the aerosol mass concentration reached 2341.3 mg/m 3 with a number concentration of 1.3 × 10 7 1/cm 3 . Moreover, aerosol emissions cannot be effectively reduced by conventional countermeasures such as a water wash or demister. , In general, aerosol emissions are usually produced by heterogeneous and homogeneous condensation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Details of the experimental parameters are summarized in Table . It should be noted that the heat exchanger and wet electrostatic precipitator shown in Figure were utilized for amine and sulfuric acid aerosol removal, , and the heat exchanger remained inactive throughout the study to prevent potential interference with the precharging enhancement for black carbon scrubbing. The wet electrostatic precipitator (WESP) was periodically activated to mitigate the risk of fan clogging due to excessive accumulation of SP-BC in the pipelines.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, 43 we have used a small-scale MSC experimental platform to investigate and evaluate the absorption performance and regeneration duty of the MSC process. 44 Simultaneously, the MSC process was modeled and studied by using Aspen Plus. As shown in Figure 3, the simulation results were all within the error bars of the experimental data, confirming the reliability of the model.…”
Section: Model Validationmentioning
confidence: 99%